(3CeGdj GHf GdTLQjs - (3GHf GdTLQj , gHI Gddg Hf Ydj Hf eMeO GdMSfj, CHh GdSYGOGJ,J (B542 (3g` s ((3eMeO Hf MSjf Hf Ydj GdYGedj s)
(3ChdgG (B:s
(3CNHQfG CHhMaU YQe Hf eMeO Hf WHQRO (B- (3GdHZOGOj bQGAI YdjI hCfG CSeY HOeTb aj Pj GdMLI CNHQfG CHhGdSYGOGJ HHZOGO bGd(B: (3GdeLdS GdChd(B: (3eSCdI s
(3ef fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQM hGedGA s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs